Open skin boats of the Aleutians, Kodiak Island, and Prince William Sound - Anichtchenko, Evguenia (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2012)
AbstractThis article examines the relationship between the open skin boat (umiak) traditions of the Unangax/Aleut who inhabited the Aleutian Islands and the Sugpiat of Kodiak Island and Prince William Sound, the two southernmost Indigenous Alaskan peoples who used such watercraft. In a larger geographical context, the Aleutian Islands and the Kodiak Archipelago form a chain of lands stretching from the Alaska Peninsula to the eastern coast of Eurasia. Drawing from archaeological and ethnographic evidence, the author discusses both technological and social aspects of open skin boats. A comparison between Sugpiaq and Unangax/Aleut boats demonstrates similarities in some structural details and leads to a discussion of technological exchange in the larger region that encompasses Southeast Alaska, Prince William Sound, the Kodiak Archipelago, the Aleutian Islands, and the Kamchatka Peninsula. The different Indigenous boat types influenced each other along a chain of overlapping related elements and structural features, rather than being adopted in each case as a complete technological corpus. This exchange occurred along routes of trade and war but ultimately created a dynamic intellectual network of watercraft technology.